Developing indicators for monitoring and evaluating the primary healthcare approach in health sciences education at the University of Cape Town, South Africa, using a Delphi technique - M I Datay; J Irlam; S Singh; F Walters; M Namane (South African Medical Association, 2023)
Background. The Faculty of Health Sciences (FHS), University of Cape Town (UCT) adopted the primary healthcare (PHC) approach as its lead theme for teaching, research and clinical service in 1994. A PHC working group was set up in 2017 to build consensus on indicators to monitor and evaluate the PHC approach in health sciences education in the FHS, UCT. Objective. To develop a set of indicators through a Delphi technique for monitoring and evaluating the PHC approach in health sciences curricula in the FHS, UCT. Methods. A national multidisciplinary Delphi panel was presented with 61 indicators of social accountability from the international Training for Health Equity Network (THEnet) for scoring in round 1. Nineteen PHC indicators, derived from a mnemonic used in the FHS, UCT for teaching core PHC principles, were added in round 2 to the 20 highest ranked THEnet indicators from round 1, on recommendation of the panel. Scoring criteria used were relevance (in both rounds), feasibility/measurability (round 1 only) and application of the PHC indicators to undergraduate and postgraduate teaching and assessment (round 2 only). Results. Of the 39 indicators presented in the second round, 11 had an overall relevance score >85% based on the responses of 16 of 20 panellists (80% response rate). These 11 indicators have been grouped by learner needs (safety of learners - 88%, teaching is appropriate to learners' needs and context - 86%); healthcare user needs (continuity of care - 94%, holistic understanding of healthcare - 88%, respecting human rights - 88%, providing accessible care to all - 88%, providing care that is acceptable to users and their families - 87%, providing evidence-based care - 87%); and community needs (promoting health through health education - 88%, education programme reflects communities' needs - 86%, teaching embodies social accountability - 86%). Conclusion. The selected indicators reflect priorities relevant to the FHS, UCT and are measurable and applicable to undergraduate and postgraduate curricula. They provided the basis for a case study of teaching the PHC approach to our undergraduate students.